An analytical calculation of the Jacobian matrix for 3D friction contact model applied to turbine blade shroud contact. (December 2016) - Afzal, Mohammad; Lopez Arteaga, Ines; Kari, Leif
Highlights: A time-discrete variant of full-3D friction contact model is reformulated. An analytical expression of the Jacobian matrix is obtained for the same. The derived Jacobian matrix significantly reduces the computation time. Forced response curves obtained using quasi and full-3D contact model are compared. Results show that a full-3D friction contact model is essential for these problems. Abstract: An analytical expression is formulated to compute the Jacobian matrix for 3D friction contact modeling that efficiently evaluates the matrix while computing the friction contact forces in the time domain by means of the alternate frequency time domain approach. The developed expression is successfully used for the calculation of the friction damping on a turbine blade with shroud contact interface having an arbitrary 3D relative displacement. The analytical expression drastically reduces the computation time of the Jacobian matrix with respect to the classical finite difference method, with many points at the contact interface. Therefore, it also significantly reduces the overall computation time for the solution of the equations of motion, since the formulation of the Jacobian matrix is the most time consuming step in solving the large set of nonlinear algebraic equations when a finite difference approach is employed. The equations of motion are formulated in the frequency domain using the multiharmonic balance method to accurately capture the nonlinear contact forces and displacements. Moreover, the equations of motion of the full turbine blade model are reduced to a single sector model by exploiting the concept of cyclic symmetry boundary condition for a periodic structure. Implementation of the developed scheme in solving the equations of motion is proved to be effective and significant reduction in time is achieved without loss of accuracy.